GRIN2A mutation and early‐onset epileptic encephalopathy: personalized therapy with memantine. (3rd March 2014) - Pierson, Tyler Mark; Yuan, Hongjie; Marsh, Eric D.; Fuentes‐Fajardo, Karin; Adams, David R.; Markello, Thomas; Golas, Gretchen; Simeonov, Dimitre R.; Holloman, Conisha; Tankovic, Anel; Karamchandani, Manish M.; Schreiber, John M.; et al.
Abstract Objective Early‐onset epileptic encephalopathies have been associated with de novo mutations of numerous ion channel genes. We employed techniques of modern translational medicine to identify a disease‐causing mutation, analyze its altered behavior, and screen for therapeutic compounds to treat the proband. Methods Three modern translational medicine tools were utilized: (1) high‐throughput sequencing technology to identify a novel de novo mutation; (2) in vitro expression and electrophysiology assays to confirm the variant protein's dysfunction; and (3) screening of existing drug libraries to identify potential therapeutic compounds. Results A de novo GRIN2A missense mutation (c.2434C>A; p.L812M) increased the charge transfer mediated by N‐methyl‐D‐aspartate receptors (NMDAs) containing the mutant GluN2A‐L812M subunit. In vitro analysis with NMDA receptor blockers indicated that GLuN2A‐L812M‐containing NMDARs retained their sensitivity to the use‐dependent channel blocker memantine; while screening of a previously reported GRIN2A mutation (N615K) with these compounds produced contrasting results. Consistent with these data, adjunct memantine therapy reduced our proband's seizure burden. Interpretation This case exemplifies the potential for personalized genomics and therapeutics to be utilized for the early diagnosis and treatment of infantile‐onset neurological disease.